LSB algorithm based on support vector machine in digital image steganography - Hussain, Hanizan Shaker; Din, Roshidi; Mustapha, Aida; Mansor, Fawwaz Zamir (UTEM, 2017)
The importance of information security in protecting data and information has increased due to the increased use of computers and the Internet. It similar with the one of exciting subfields of information security called information hiding. Information hiding is a technology where the secret-messages are hidden inside other files (e.g image files). One of the areas that are popular now applying this technology is digital image steganography (image steganography). In this paper proposed StegaSVM-Shifted LSB model that has been proposed that utilize HVS and embedding technique through Shifted LSB showed a good performance. This can be seen when PSNR record high value, where it displays a good quality cover-image.